Pemeriksaan Tekanan Darah, Golongan Darah, Kadar Hemoglobin untuk Mengetahui Kelayakan Donor Darah - Adita Puspitasari Swastya Putri, Adita Puspitasari Swastya Putri (Universitas Nusantara PGRI Kediri, 2024)
Blood donation is the process of distributing blood which is a humanitarian activity. Prospective donors must first undergo a health examination and medical consultation to determine their suitability for blood donation. The aim of this Community Service is to determine the frequency distribution of blood pressure, blood type, hemoglobin levels and the health conditions of residents in Tlogosari Wetan Village, Pedurungan District, Semarang City. Community service activities are carried out through several stages namely the planning, implementation and evaluation stages. At the planning stage, the target audience is determined. The implementation stage is carried out with a flow starting from a blood type examination, hemoglobin examination, body weight and blood pressure measurements. The evaluation stage is carried out after processing data from all examination results to determine the suitability of blood donation. The result is that the majority of residents in Tlogosari Wetan Village, Pedurungan District, Semarang City have blood type O is 29 (58%) people, abnormal hemoglobin levels is 28 (56%) people, appropriate body weight is 45 (90%) people, normal blood pressure is 27 (54%) people, not feasible for blood donation is 35 (70%) people. In the upcoming Community Service activities, it is hoped that blood donation activities can be carried out for community members who meet the requirements as blood donation in order to increase the interest and experience of people who have never donated blood.